IMPLEMENTASI PENANGANAN KRISIS AIR BERSIH DI DESA SUKAGALIH, KECAMATAN JONGGOL - Ayu Herzanita; Azaria Andreas; Nuryani Tinumbia; Dwi Ariyani (Program Studi Teknik Sipil Fakultas Teknik Universitas Pancasila, 2024)
The clean water crisis that occurred on the island of Java was predicted 10 years ago. The increasing population plus an inadequate water distribution network system is the root of the clean water problem in Sukagalih Village, Jonggol District. On the other hand, the water discharge produced by springs always fluctuates according to changing seasons. This research aims to plan a clean water system network that connects springs with water collection points in Hamlet 2, Sukagalih Village. The objectives of this research include analyzing the water pipe route alignment, analyzing the costs and duration of work implementation, and implementing the planning results into real construction in the field. The research method used is construction planning based on the last planner system (LPS). This approach is chosen so that the planning process can take place flexibly and can be updated following developments in conditions in the field. The research results show that the costs required to carry out the work are Rp. 14,710,000. Meanwhile, the time required to complete this work is 8 weeks (2 months). Specifically for pipe installation work, it takes 3 weeks. The results of checking the system that was built went well and water from the spring flowed smoothly to the planned water collection point using a water torrent.